2012
DOI: 10.1186/1477-7827-10-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of HOXA11 in the mid-luteal endometrium from women with endometriosis-associated infertility

Abstract: BackgroundA decrease in HOXA11 expression in eutopic mid-secretory endometrium has been found in women with endometriosis-associated infertility.MethodsUsing Real-time quantitative PCR (RQ-PCR) and western blotting analysis we studied the HOXA11 transcript and protein levels in mid-luteal eutopic endometrium from eighteen infertile women with minimal endometriosis, sixteen healthy fertile women and sixteen infertile women with fallopian tubal occlusion from the Polish population. We also evaluated transcript l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 45 publications
3
61
1
Order By: Relevance
“…To demonstrate the utility and reliability of the SNAIL1-CBR reporter in vivo , we measured tissue-specific bioluminescence intensity during both physiologic and pathologic EMT processes known to be SNAIL1-dependent. Placental development is a robust EMT process and SNAIL1 has been implicated in trophoblast differentiation and uterine invasion [22, 23]. At 7.5 days post coitus (dpc) when trophoblast EMT is high [24], uterine SNAIL1-CBR signal was 5 fold higher compared to the basal signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To demonstrate the utility and reliability of the SNAIL1-CBR reporter in vivo , we measured tissue-specific bioluminescence intensity during both physiologic and pathologic EMT processes known to be SNAIL1-dependent. Placental development is a robust EMT process and SNAIL1 has been implicated in trophoblast differentiation and uterine invasion [22, 23]. At 7.5 days post coitus (dpc) when trophoblast EMT is high [24], uterine SNAIL1-CBR signal was 5 fold higher compared to the basal signal (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The normal connecting piece and upper midpiece contain a small portion of cytoplasm with a few endoplasmic reticulum vesicles. The midpiece is the major site of water influx and cell volume regulation, and these vesicles are important when sperm face hypo-osmotic challenges 89. The cytoplasmic droplet is indeed, really important for sperm function given that spermatozoa without it were immotile due to a defective spermatogenesis 90.…”
Section: Main Factors Affecting Sperm Motilitymentioning
confidence: 99%
“…In women with endometriosis, Wu et al showed increased DNMT3A and DNMT3B mRNA in ectopic endometriotic epithelium (33). More recently Szczepanka described elevated DNMT3A mRNA expression in the eutopic endometrium from women with endometriosis, although the other DNMTs remained unchanged (56). In contrast, Van Kaam observed little change in DNMT3B in whole tissue explants (30).…”
Section: Discussionmentioning
confidence: 99%